An electron beam ion trap and source for re-acceleration of rare-isotope ion beams at TRIUMF - Blessenohl, Michael A.; Dobrodey, Stepan; Warnecke, Christian; Rosner, M. K.; Graham, L.; Paul, S.; Baumann, T. M.; Hockenbery, Z.; Hubele, Renate; Pfeifer, Thomas; Ames, F.; Dilling, J.; et al. (Review of scientific instruments, 2018)
Electron beam driven ionization can produce highly charged ions (HCIs) in a few well-defined charge states. Ideal conditions for this are maximally focused electron beams and an extremely clean vacuum environment. A cryogenic electron beam ion trap fulfills these prerequisites and delivers very pure HCI beams. The Canadian rare isotope facility with electron beam ion source-electron beam ion sources developed at the Max-Planck-Institut für Kernphysik (MPIK) reaches already for a 5 keV electron beam and a current of 1 A with a density in excess of 5000 A/cm2 by means of a 6 T axial magnetic field. Within the trap, the beam quickly generates a dense HCI population, tightly confined by a space-charge potential of the order of 1 keV times the ionic charge state. Emitting HCI bunches of ≈107 ions at up to 100 Hz repetition rate, the device will charge-breed rare-isotope beams with the mass-over-charge ratio required for re-acceleration at the Advanced Rare IsotopE Laboratory (ARIEL) facility at TRIUMF. We present here its design and results from commissioning runs at MPIK, including X-ray diagnostics of the electron beam and charge-breeding process, as well as ion injection and HCI-extraction measurements.
Gesehen am 24.06.20204